Does sexualization in video games cause harm in players? A meta-analytic examination. (October 2022) - Ferguson, Christopher J.; Sauer, James D.; Drummond, Aaron; Kneer, Julia; Lowe-Calverley, Emily
Abstract: Whether video games with sexualized content do or do not relate to mental health and body image problems in players, and/or sexualization and hostility toward women, is an issue of broad public interest. However, evidence from empirical studies has generally been mixed. To examine this issue, we explored the degree to which sexualization in games was related to both well-being/body dissatisfaction and sexism/misogyny among players in two separate meta-analyses. Results revealed that sexualization in games was neither related to well-being/body dissatisfaction ( r = 0.082, k = 10, n = 2, 010, p = .066) nor sexism/misogyny ( r = 0.040, k = 15, n = 15, 938, p = .070). Better designed studies, and those that showed less evidence for researcher expectancy effects (for sexism/misogyny outcomes), tended to find less evidence for effects. As appears commonly in other realms of media effects, the evidence is weak that sexualized games influence player attitudes and behavior. Highlights: Whether sexualization in video games causes negative outcomes is a matter of concern. Meta-analysis examined sexualization effects on misogynistic and mental health outcomes. Exposure to sexualization in games was not found to be associated with negative outcomes. Better quality studies were less able to find evidence for effects.